Morfofisiologia da cultura de batata submetida a diferentes regimes hídricos - Fernández, Sebastián Casanova (2008)
The objective of this work was: (i) to study morpho-physiological and yield modifications in two potato cultivars (Chieftain and Iporá) under different irrigation managements and; (ii) to determine the actual crop evapotranspiration. Two experiments were carried out during 2006/07 growth season in a rainout shelter located at INIA (National Institute of Agricultural Research) in Uruguay. One of these experiments was carried out in a set of 12 drainage lysimeters whith four irrigation managements: (i) 2003/04 rainfall + 216 mm (irrigation from the maximum daily crop evapotranspiration), (ii) 2003/04 rainfall, (iii) 2003/04 rainfall + one irrigation of 25 mm (when the accumulated maximum daily crop evapotranspiration reached 90 mm), and (iv) 2003/04 rainfall + 143 mm of irrigation applied from the maximum daily crop evapotranspiration, after the crop tuberization stage. The maximum daily crop vapotranspiration was estimated using the FAO Penman-Monteith equation. A second experiment was carried out in an area of 90 m2, where the Chieftain and Iporá were studied under two irrigation managements: (i) 2003/04 rainfall + 246 mm (irrigated treatment) and (ii) 2003/04 rainfall + one irrigation of 25 mm (when the accumulated maximum daily crop evapotranspiration reached 90 mm). The results indicated that based on the morpho-physiological parameters studied, the leaf area, the transpiration and the total plant photosynthesis are better correlated with adaptations of potatoes crops to the water deficit and resulted in a direct relationship with the crop yield. The two potatoes cultivars (Chieftain and Iporá) showed modifications in: length of growth duration, leaf area, number of principal stems, plant height, and plant transpiration. The potatoes plants developed in lysimeters did not show differences in yield components but differences were observed in potato commercial classes. In the second experiment all the yield components were modified by the irrigation managements. Differences in commercial yield and total number of plant tubers were observed between the Chieftain and Iporá cultivars. The actual crop evapotranspiration values observed in the rainfall 2003/04 + 216 mm and rainfall 2003/04 treatments are directly related to leaf area and water content of soil.